Pressure-based large-eddy simulation of under-expanded hydrogen jets for engine applications - Ballatore, A.; van Oijen, J.A. (International journal of hydrogen energy, 2024)
An assessment of Large-Eddy Simulations (LES) of non-reactive under-expanded hydrogen jets by using a pressure-based algorithm is presented. Such jets feature strong compressible discontinuities often considered to be best dealt with by a density-based solver. The crucial contribution of this work is to evaluate the suitability of the pressure-based solver to correctly describe the flow field of gaseous hydrogen jets for engine applications, despite the presence of shock waves in the under-expanded near-orifice region. Inherently, the paper aims at providing guidance on the corresponding numerical aspects to simulate these flows. Hydrogen jets in an argon atmosphere at three different injection pressures are simulated and the results are compared to experiments in literature. Jet tip penetration and cone angle are the main investigated parameters. A good match is found, confirming the solidity of the proposed model. Different LES sub-grid scale models and discretisation schemes are then investigated in order to find the best approach in terms of accuracy and required computational cost. In particular, it is found that the WALE model coupled with a 4th-order cubic scheme for the convective terms yields the most suitable configuration. •Our model correctly describes the mixing of H2 jets for DI-CI engine applications.•Pressure-based solvers can be used with reasonable accuracy for under-expanded flows.•Under-relaxation factors help such p-based algorithm improving the shock resolution.•The WALE model with 4th-order cubic convective schemes delivers the most accurate results.